2019
DOI: 10.3390/ma12223760
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Release from Two High-Viscosity Glass Ionomers after Exposure to Fluoride Slurry and Varnish

Abstract: The effect of brushing with different fluoride slurries on the fluoride release (FR) of different high-viscosity glass ionomer cements (GICs) was investigated. Fifty-eight discs were fabricated from two high-viscosity GICs (GC Fuji IX (F9) and 3M ESPE Ketac-fil (KF)). Five specimens from each brand were used to measure Vickers microhardness and the remaining were randomly assigned to one of four groups (n = 6) based on two-factor combinations: (1) fluoride concentration in the abrasive slurry (275 or 1250 ppm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“… 24 The study by Hani M. Nassar showed that the amount of fluoride released from glass ionomer-based materials were decreased after undergone brushing since high fluoride release only in early period and abated significantly to reach an ambient sustained fluoride release over time. 32 Supported by the study of Wiegand A. which stated that brushing leads to a reduction of the surface concentration of fluoride. 33 Consequently, the amount of fluoride released significantly decreased after the brushing simulation in all materials except Z350XT.…”
Section: Discussionmentioning
confidence: 99%
“… 24 The study by Hani M. Nassar showed that the amount of fluoride released from glass ionomer-based materials were decreased after undergone brushing since high fluoride release only in early period and abated significantly to reach an ambient sustained fluoride release over time. 32 Supported by the study of Wiegand A. which stated that brushing leads to a reduction of the surface concentration of fluoride. 33 Consequently, the amount of fluoride released significantly decreased after the brushing simulation in all materials except Z350XT.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the higher exposition of filler particles provided increased surface hardness values in the conventional resin composite tested. Also, a glass ionomer cement is softer than other restorative materials [38]. In this way, the resin coat remotion in the conventional glass ionomer cement post-radiation exposed a softer and more hydrophilic material with a decreased hardness and increased wettability.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that glass ionomer can inhibit the growth of Streptococcus mutans and Lactobacillus , therefore, it can prevent secondary caries to a certain extent but cannot inhibit the growth of Candida albicans [ 33 ], one of the pathogenic bacteria responsible for root caries [ 34 ]. Since the release of fluoride ions is related to the glass ionomer composition, most high-viscosity and resin-modified glass ionomers have a lower total fluoride ion release than the conventional ones [ 35 ], therefore, conventional glass ionomers have better antibacterial properties [ 36 ]. The remineralization properties of glass ionomer are also related to the release of fluoride ions [ 37 ].…”
Section: Currently Available Restorative Materials For the Elderlymentioning
confidence: 99%